THE HISTORY OF ESTABLISHMENT OF THE NATURAL SOURCES DOSIMETRY LABORATORY IN THE INSTITUTE OF RADIATION HYGIENE AFTER PROFESSOR P.V. RAMZAEV, 1987–2005 - I. P. Stamat; E. P. Lisachenko; N. A. Koroleva (Радиационная гигиена)
The first 5–7 years of the period under review in the history of the Natural Sources Dosimetry Laboratory happened to be in very hard period, which had a time the entire country. A severe funding reduction of the Institute in the 90-s created a threat of loss of the most active and highly professional middle-aged specialists. In these conditions, the only and the most efficient way to maintain Institute as a scientific establishment was to organize the Federal Radiological Center under the guidance of Dr. A.N. Barkovskiy. The Federal Radiological Center consisted of the all physical laboratories, including the Natural Sources Dosimetry Laboratory, without government funding. Nevertheless, as it is shown below, this period was the most fruitful for theoretical and experimental researches, and for development of legal documents and instructional guidance documents. Over these years, more than 10 sanitary regulations and hygienic standards, and more than 20 guidance documents were developed and implemented. Doses of the population due to the natural exposure data-collecting system on the base of federal statistical observation №4-DOZ form were designed. At this period, the first Federal Target Program «Radon» and the System of radiation and hygienic passportization of organizations and territories were developed and authorized. Dr. E.M. Krisiuk was fully engaged in these activities. In these years a great number of non-nuclear companies were examined. Large-scale studies of levels of exposure of the population on specific territories were conducted. The paper examines a summary of the main results, which were obtained in the most important areas of research and practical studies in the period under review.